Pengaruh Pemberian Media Terhadap Pelaksanaan Inisiasi Menyusu Dini di Empat Wilayah Kerja Rumah Sakit Bersalin Makassar - Hasyati, Hasyati; Idris, Fairus Prihatin; Yusriani, Yusriani (Window of Health : Jurnal Kesehatan, 2019)
Education in breastfeeding is the most effective intervention methods increases the initiation of breastfeeding in the short term. Methods of educational interventions in the mother not only aims to improve the knowledge and skills of the mother but also affect their behavior in breastfeeding. Education about breastfeeding and frequent breastfeeding during prenatal and intrapartum taught by someone who has expertise in lactation management with a structured educational system. This research was conducted with the aim to analyze the effect of the use of media to the implementation of early initiation of breastfeeding in the four regions of the working maternity hospital in Makassar The method used in this research is quantitative approach with Quasi-experiments, this study uses primary data by as many as 66 people Third Trimester Pregnancy (Pregnancy 40-42 weeks of age), in which 33 people for the intervention group and 33 for the control group data were analyzed using the Mann Whitney test. Results showed variable mother knowledge (p = 0.000 <Î± = 0.05) and the mother's attitude (p = 0.000 <Î± = 0.05), that: (1) There is the influence of media on the implementation of early initiation of breastfeeding rated of knowledge, (2) There is the influence of media on the implementation of early initiation of breastfeeding rated of attitude This means that knowledge, attitudes capable of encouraging an increase in the implementation of Early Initiation of Breastfeeding. A good knowledge owned by the mother may affect participation in conducting Early Initiation of Breastfeeding. Knowledge, Attitude Mother of early initiation of breastfeeding is very important to support mothers in participating do IMD. As well as the family also must have good knowledge and attitudes that support in providing health education to improve the mother's knowledge.